Radio spot on roselle (Hibiscus sabdariffa) - Sana, Halizata; Borelli, Teresa (2023)
Part of a larger information campaign on neglected and underutilized species (NUS), this radio campaign uses simple, colloquial language and daily life settings to promote NUS that were once common on farms and in the diets of people living in Burkina Faso and Niger. The radio campaign aims to promote these nutritious crops, which can be included in sustainable, climate-smart agriculture as well as become potential sources of income.